2018
DOI: 10.1055/s-0038-1675344
|View full text |Cite
|
Sign up to set email alerts
|

Structured Training for Fetal Diagnostic Skills in a Maternal-Fetal Medicine Fellowship

Abstract: Objective  The American Institute of Ultrasound in Medicine has described what constitutes a detailed fetal anatomic examination but what comprises an appropriate physician training program has not been described. The purpose of this paper is to describe a highly-structured program developed by our center to train maternal-fetal medicine fellows in a systematic approach to fetal diagnostic imaging. Study Design  We describe this approach in three phases. Phase I: Development of Skills as a Perinatal Sonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…3 Calls for standardization of ultrasound education in the United States date back to the 1980s, 14 and multiple training curricula have been proposed and evaluated by various institutions over the past three decades. [15][16][17] An important limitation of previous efforts is designing curricula within individual institutions rather than developing a national blueprint endorsed by multiple national organizations. Without such endorsement, efforts often lack sustainability and an independent evaluation standard to assess successes and areas for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Calls for standardization of ultrasound education in the United States date back to the 1980s, 14 and multiple training curricula have been proposed and evaluated by various institutions over the past three decades. [15][16][17] An important limitation of previous efforts is designing curricula within individual institutions rather than developing a national blueprint endorsed by multiple national organizations. Without such endorsement, efforts often lack sustainability and an independent evaluation standard to assess successes and areas for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound plays a central role in diagnosis and management of a broad range of obstetric and gynecologic conditions in both inpatient and outpatient settings and is a common part of residents' work 3 . Calls for standardization of ultrasound education in the United States date back to the 1980s, 14 and multiple training curricula have been proposed and evaluated by various institutions over the past three decades 15–17 . An important limitation of previous efforts is designing curricula within individual institutions rather than developing a national blueprint endorsed by multiple national organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, formal incorporation of advanced ultrasound trainingincluding Doppler studies and fetal anatomic surveys -is not included in the Accreditation Council for Graduate Medical Education (ACGME) directive of any medical training program other than fellowship training in MFM (Table 1). [4][5][6][7][8][9][10][11][12][13] Prior studies have demonstrated improved diagnosis of fetal anomalies when ultrasounds are interpreted by MFM physicians compared to other providers. 14,15 However, MFM providers are known to be concentrated in certain parts of the country, and there are many areas where traditional obstetric ultrasound care by an MFM physician is unavailable.…”
Section: Introductionmentioning
confidence: 99%